NEW INSIGHTS INTO CYTOMEGALOVIRUS INFECTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
CMVI is an infection caused by a pathogen from the beta-herpesvirus group, characterised by diverse manifestations ranging from asymptomatic to generalised course with severe damage to the CNS and other organs. CMV infection is widespread [5,6,7].